Nickel-N,N'-bis(salicylidene)-1,3-propanediamine (Ni-Salpn) film-modified electrodes. Influence of electrodeposition conditions and of electrode material on electrochemical behaviour in aqueous solution - Martin, Cibely S. [UNESP]; Gouveia-Caridade, Carla; Crespilho, Frank N.; Constantino, Carlos J.L. [UNESP]; Brett, Christopher M.A. (Elsevier, 2015)
Abstract Modified electrodes based on films of Schiff base complexes are excellent candidates for sensing applications. The influence of the electrode material, glassy carbon, platinum, gold or indium tin oxide, on the electrodeposition of nickel-N,N'-bis(salicylidene)-1,3-propanediamine (Ni-Salpn) films in 1,2-dichloroethane (DCE) was investigated, and their electrochemical behaviour was evaluated by cyclic voltammetry and electrochemical impedance spectroscopy. The effect of the electrodeposition potential and electrodeposition time on the electrochemical behaviour of Ni-Salpn was examined using glassy carbon as substrate. The film growth process was investigated using the electrochemical quartz crystal microbalance and UV-vis absorption spectroscopy and structural differences between the Ni-Salpn complex and the Ni-Salpn film were examined by micro-Raman spectroscopy. The results demonstrate that the electrodeposition mechanism is independent of the electrode material, but that the nature of the substrate material influences the rate of film growth, the electrochemical behaviour and the stability of the film-modified electrodes in aqueous solution. Counteranion insertion during oxidation can break the bonds between the complexes in the stacked Ni-Salpn film structure and cause both mass loss and blockage of the redox metal centre activity, but these effects are small in thin films.
Keywords: Electrodeposition; EQCM; Influence of electrode material; Ni-Salpn films; UV-vis and Raman spectroscopy